Software architectures for health care cyber‐physical systems: A systematic literature review. Issue 7 (15th January 2018) - Plaza, Andrea M.; Díaz, Jessica; Pérez, Jennifer
Abstract: Cyber‐physical systems (CPS) refer to the next generation of Information and Communication Technology systems that mainly integrate sensing, computing, and communication to monitor, control, and interact with a physical process to provide citizens and businesses with smart applications and services: health care, smart homes, smart cities, and so on. In recent years, health care has become one of the most important services due to the continuous increases in its costs. This has motivated extensive research on health care CPS, and some of that research has focused on describing the software architecture behind these systems. However, there is no secondary study to consolidate the research. This paper aims to identify and compare existing research on software architectures for health care CPS in order to determine successful solutions that could guide other architects and practitioners in their health care projects. We conducted a systematic literature review and compared the selected studies based on a characterization schema. The research synthesis results in a knowledge base of software architectures for health care CPS, describing their stakeholders, functional and non‐functional features, quality attributes architectural views and styles, components, and implementation technologies. This systematic literature review also identifies research gaps, such as the lack of open common platforms, as well as directions for future research. Abstract : This paper aims to identify and compare existing research on software architectures for health care Cyber‐Physical Systems to determine successful solutions that could guide other architects and practitioners on their health care projects. We conducted a systematic literature review and the research synthesis results in a knowledge base of software architectures for health care CPS by describing their stakeholders, functional and non‐functional features, quality attributes, architectural views and styles, components, and implementation technologies. This systematic literature review also identifies research gaps and future research directions.